Drag each expression to show whether it is equivalent to 54x + 18, 18(3x – 1), or (6 • 9x) + (6 • 1).

expressions: A-54x B-(6 • 9x) + (6 • 3) C-54x + 6 D-3(18x+2) E-18(3x+1) F-(9*6x)-(9*2)

Respuesta :

Answer with explanation:

1.We have to find equivalent expression of ⇒ 54 x+18

These are the equivalent expression of

=3×3×3×2× x+3×3×2

=3×3×2×(3 x+1)

=18×(3 x+1)

2.⇒Equivalent expression of→ 18×(3 x-1)

=18× 3 x -18------[Using commutative property of Multiplication with respect to subtraction)

=54 x-18

3.⇒Equivalent expression of→6×9 x+ 6×1

                  =54 x +6

⇒Option B

6×9 x +6×3-------equivalent expression of →54 x+18

⇒Option C

54 x+6-------equivalent expression of →6×9 x+ 6×1

⇒Option D

3×(18 x+2)------equivalent expression of →6×9 x+ 6×1

⇒Option F

9×6 x -9×2-------equivalent expression of → 18×(3 x-1)

Hope this helps! pls mark brainliest

Ver imagen SeanChua101
ACCESS MORE